COVID-19 Pandemic in ASEAN Region and Implication in Dentistry - Suttagul, Kanokwan; Sirichitra, Vinai (Open Access Macedonian Journal of Medical Sciences, 2020)
The coronavirus disease (COVID-19) has spread globally and has influenced every aspect of life worldwide. In the ASEAN region, at present, many nations are still locked the academic organizations, shopping malls, events, and activities, and banks and airports are shut down to prevent the spread of the COVID-19 infection. COVID-19 has affected dental practice, and, in many countries, dentists are affected by COVID-19, leading to deaths. The dental treatments should be done with high standards of care and infection control by following proper recommendations. Personal protective equipment, patient screening, hand hygiene practices, mouth rinsing, disposable instruments, and use of rubber dam, reducing ultrasonic instruments use, treating suspected or confirmed COVID-19 patients in separate rooms, and disinfection of the inanimate surfaces helps in protecting clinicians and patients.